Penyuluhan Pentingnya Menjaga Perilaku Hidup Bersih dan Sehat pada Siswa dalam Rangka Kegiatan Masa Pengenalan Lingkungan Sekolah (MPLS) di SD Negeri Krebet, Bantul Yogyakarta - Pusparini Anggita Ayuningtyas; Masta Hutasoit; Miftafu Darussalam; Ferianto; Reno Sumiyar Rini; Anastasia Suci; Rika Suryana (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2026)
Clean and Healthy Living Behavior (CHLB/PHBS) is a fundamental component in shaping an individual's health quality from an early age. However, in many elementary schools, including SD Negeri Krebet, Bantul, students' understanding of PHBS remains limited. This community service activity aimed to improve the knowledge of first to third-grade students about PHBS through educational and engaging health counseling. The intervention included interactive lectures and animated video screenings, integrated into the School Orientation Program (MPLS). A total of 77 students participated in the activity, with 25 randomly selected for pre-test and post-test evaluation. Data analysis used the Wilcoxon test. The average pre-test score was 6.75, increasing to 8.28 in the post-test. All students showed improved knowledge (positive ranks: 25), with no declines or unchanged results. The p-value of 0.000 indicated a statistically significant impact of the intervention. This improvement was reflected not only in numerical data but also in students' enthusiasm during the activity. The visual and communicative delivery helped students better grasp the PHBS concept. As an output, the activity produced an educational video published on social media as part of health information dissemination. Thus, this program effectively increased PHBS knowledge among elementary school students and can serve as a replicable model for health education in other schools.